Early Christianity in Athens, Attica, and Adjacent Areas : From Paul to Justinian I (1st-6th cent. AD) - Breytenbach, Cilliers (Ancient Judaism and Early Christianity, 2022)
This volume focuses on the rise and expansion of Christianity in Athens, Attica, and adjacent areas, from the Pauline mission until the closing of the philosophical schools under Justinian I. It takes into account all relevant literary, epigraphical, and archaeological evidence.